Theoretical study on 2D photoelectric emission of GaN nanorod array and nanocone array photocathode. (9th September 2020) - Zhang, Xingyue; Liu, Lei; Lv, Zhisheng; Lu, Feifei; Tian, Jian
Summary: In order to improve the photoemission performance of gallium nitride (GaN) ultraviolet vacuum photoelectric devices and to obtain GaN photocathode with high quantum efficiency in this paper. The photoelectric emission theoretical models of GaN nanorod array and GaN nanocone array are constructed, and the models are simulated by COMSOL Multiphysics and MATLAB software. By changing the structure of the photocathode emission layer, the low photoemission performance of the conventional reflection‐mode thin‐film photocathode can be improved. After calculating and analyzing the influence of the geometric parameters of the nanorod array on its quantum efficiency (QE), it is found that the nanorod array has the best diameter and spacing to maximize its QE, and the nanocone array can also achieve high QE under some conditions. In addition, the high QE GaN nanorod array and nanocone array structures obtained in this article can provide some references for the production and manufacture of high‐performance GaN photocathode. Abstract : The theoretical models of photoelectric emission of GaN nanorod array and GaN nanocone array are constructed. We use COMSOL Multiphysics software and MATLAB for simulation calculation. High quantum efficiency GaN nanorod array and nanocone array structures are obtained, which are superior to the conventional reflection‐mode GaN thin‐film photocathode.